Analysis of bone quality formation in sinus lifts with immediate implants - Sofía Soler-Alcaraz; Yolanda Guerrero-Sánchez; Osmundo Gilbel Del Águila; Juan Carlos Bernabeu-Mira; Fabio Camacho-Alonso (BMC, 2024)
Abstract Sinus lift surgeries are part of the daily practice of dentists. This study evaluates the long-term structure of the bone placed in sinus lifts through the fractal dimension. We conducted a retrospective study on a sample of 35 patients with 51 sinus lifts performed using a lateral window approach and filling material placement. We radiologically analyzed the graft bone to observe its evolution up to one and a half years after the surgical procedure. The obtained results were the average area of the sinuses analyzed was 1401.96 mm2, with a mean area occupied by the filling material of 297.75 mm2. Significant differences are observed when comparing the fractal dimension values obtained on the initial day and one year after prosthesis loading. Similarly, when comparing the values of the area occupied by the biomaterial at the start day and one year after prosthesis loading, significant differences are also obtained (p-value < 0.001). In conclusion, the filling material used in the lateral window sinus lift procedure undergoes significant resorption and shows changes in the fractal dimension.